Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/978-3-319-16172-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Identities of Engineers

Abstract: Abstract:In 2007 Gary Downey, Juan Lucena and Carl Mitcham argued that a "key issue in ethics education for engineers concerns the relationship between the identity of the engineer and the responsibilities of engineering work". They suggested that "one methodological strategy for sorting out similarities and differences in engineers' identities is to ask the 'who' question. Who is an engineer? Or, what makes one an engineer?" (Downey, Lucena & Mitcham, 2007). This chapter explores these questions of who is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Throughout we use the term 'designer' to refer to design practitioners with a formal design engineering education. This definition reflects the research sample as well as accounting for the context and community of practice relevant to professional identification (Baumeister & Muraven, 1996;Murphy et al, 2015). The results show substantial differences in the perspectives of professors and managers with respect to designers, particularly surrounding the prioritisation of creativity verses responsibility and customer service.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Throughout we use the term 'designer' to refer to design practitioners with a formal design engineering education. This definition reflects the research sample as well as accounting for the context and community of practice relevant to professional identification (Baumeister & Muraven, 1996;Murphy et al, 2015). The results show substantial differences in the perspectives of professors and managers with respect to designers, particularly surrounding the prioritisation of creativity verses responsibility and customer service.…”
Section: Introductionmentioning
confidence: 92%
“…The general construction of Professional Identity (PI) formally begins during higher education. Consequently, professors play a pivotal role in the initial development of their students' PI, based on their teaching of the norms they believe a student should adhere to, reinforced via academic assessment (Murphy, Chance, and Conlon 2015). As a result, students tend to align their perception of a profession with those of their professors (Trede, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The value of Jamison et al's (2014) tripartite analysis of engineering education is that it allows us to link the different paradigms of engineering education to different conceptions of what it means to be an engineer, thus positing a generative view of engineering identity. By engineering identity is understood who counts as an engineer, what does performing the role of an engineer entail and what are the responsibilities of engineers (Murphy et al, 2015).…”
Section: Generative Engineering Identitymentioning
confidence: 99%
“…Recent literature has indicated that when engineering educators and students fail to recognize the persistence of a cultural influence in engineering education, undesirable consequences can result [51]. For example, a lack of culturally-responsive and holistic curricular content may limit students' understanding of their future professional roles [52], which may hinder students' sense of "ownership" (i.e., self-efficacy) of their professional actions and beliefs [53], [54]. In addition, a lack of social capital for underrepresented groups in engineering can lead to challenging university transitions [55], which may influence high attrition rates [56].…”
Section: Preliminary Considerations For Appropriate Interventions For Hc In Engineeringmentioning
confidence: 99%